STUDI PENGGUNAAN LOPINAVIR/RITONAVIR PADA PASIEN COVID-19 DERAJAT RINGAN-SEDANG DENGAN KOMORBID HIPERTENSI DAN DIABETES MELLITUS - Didik Hasmono; Agriawan Sudirman; Muhammad Nashrullah; Ruddy Hartono; Mohammad Subhan (Jurnal Kesehatan, 2023)
Lopinavir/Ritonavir is proposed as one of the therapy for Covid-19 patients based on the ability to reduce viral load. Bhayangkara Hospital Surabaya is one of the hospitals with quite a lot of Covid-19 patients in Surabaya. The research aimed to determine the effectiveness, outcome, and evaluate side effects of Lopinavir/Ritonavir in mild to moderate Covid-19 patients with comorbid hypertension and diabetes mellitus at Bhayangkara Hospital Surabaya. This was an observational study that collected data retrospectively at Bhayangkara Hospital Surabaya. Patient data had to meet the requirements for inclusion criteria, which were patients treated with Lopinavir/Ritonavir for a Covid-19 mild to moderate with comorbid hypertension and diabetes mellitus. Data were obtained from 18 patient medical records and then processed descriptively. The results showed that 7 patients (39%) received therapy A with 11 days of treatment, 4 patients received therapy B (22%) with 12 days of treatment, 1 patient (11%) received therapy C with 18 days of treatment, and 6 patients (28%) on D therapy with 14 days of treatment. Patients experiencing effects of gastrointestinal disturbances such as nausea (22%), and diarrhea (11%). Lopinavir/Ritonavir in therapy A is the most effective when viewed from the length of treatment, which is 11 days. Therapy B, C, and D were considered effective as seen from the results of RT-PCR which showed negative results, namely 100%. Therapy D is the most effective chest X-ray repair, which is 50%. Side effects of Lopinavir/Ritonavir were gastrointestinal disturbances, namely nausea (22%), and diarrhea (11%), while hepatotoxicity was not found.